Microalgal biorefineries - Ferreira, Alice (2020)
ABSTRACT: Microalgae-based bioproducts remain expensive mainly due to microalgae cultivation, harvesting, and downstream processing costs. Nonetheless, microalgae are a high potential source of several biofuels, biofertilizers, and bioproducts (e.g., carbohydrates, long-chain fatty acids, pigments, and proteins), which can provide important nutritional, cosmetical, pharmaceutical, and health benefits. In addition, they are able to perform wastewater bioremediation and carbon dioxide mitigation. This not only contributes to a more sustainable microalgae production, with environmental benefits, but also offers cost savings on the whole process. Hence, from these small cellular factories, a large source of compounds and products can be obtained, providing a real microalgal-based biorefinery. This type of approach is crucial for the full application and commercialization of microalgae in a large range of products and industries, with added benefits for bioeconomy and society in general. This chapter addresses the potential transformation of microalgal biomass into a wide range of marketable products, presenting examples of experimental microalgae-based biorefineries grown in an autotrophic mode at a laboratory scale.